The nexus between social grants and participation rates: Dynamics across generations in the South African labour market - Rulof Burger; Dieter von Fintel; Carola Grün (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2010)
This paper will have a closer look at the role of South African welfare programs on the labour supply decision across generations. From a theoretical point of view, a change in non-labour household income will affect the decision to participate in the labour market. Previous studies have focused on prime age adults and elderly and could confirm a significant decrease in labour supply of individuals living in a pensioner's household. However, past research did not look at the intergenerational pattern and broader socio-economic conditions when evaluating the impacts of social grants. Our preliminary results suggest that the behavioural response to welfare programs differs by age group. In particular, labour supply of the young living in a pensioner's household has increased. Also, intergenerational differences in participation rates can be explained by educational policies, designed specifically to address over-age students in the public schooling system.
Keywords: J22; H53; 330; labour market participation; social grants; South Africa